Clinical target volume segmentation for stomach cancer by stochastic width deep neural network. Issue 4 (12th March 2021) - Xu, Lei; Hu, Junjie; Song, Ying; Bai, Sen; Yi, Zhang
Abstract : Purpose: Precise segmentation of clinical target volume (CTV) is the key to stomach cancer radiotherapy. We proposed a novel stochastic width‐deep neural network (SW‐DNN) for better automatically contouring stomach CTV. Methods: Stochastic width‐deep neural network was an end‐to‐end approach, of which the core component was a novel SW mechanism that employed shortcut connections between the encoder and decoder in a random manner, and thus the width of the SW‐DNN was stochastically adjustable to obtain improved segmentation results. In total, 150 stomach cancer patient computed tomography (CT) cases with the corresponding CTV labels were collected and used to train and evaluate the SW‐DNN. Three common quantitative measures: true positive volume fraction (TPVF), positive predictive value (PPV), and Dice similarity coefficient (DSC) were used to evaluate the segmentation accuracy. Results: Clinical target volumes calculated by SW‐DNN had significant quantitative advantages over three state‐of‐the‐art methods. The average DSC value of SW‐DNN was 2.1%, 2.8%, and 3.6% higher than that of three state‐of‐the‐art methods. The average DSC, TPVF, and PPV values of SW‐DNN were 2.1%, 4.0%, and 0.3% higher than that of the corresponding constant width DNN. Conclusions: Stochastic width‐deep neural network provided better performance for contouring stomach cancer CTV accurately and efficiently. It is a promising solution in clinical radiotherapy planning for stomach cancer.